Social Relations of Drug Abusers (A Study on Alumni and Students of The University of North Sumatra) - Nur Islamiah, Indah; Marhaeni Munthe, Hadriana; Elida, Linda; Badaruddin, Badaruddin; Hafi, Bisru (International Journal of Social Science, Education, Communication and Economics, 2024)
The phenomenon of drug abuse that occurs in the younger generation is increasingly worrying, not only occurs in ordinary people but has also spread to various professions and involves students or students. Previously there was a case of arrest and raids carried out in the USU campus environment and found two suspects BS and NK who carried 740 grams and 850 grams of marijuana. The purpose of this study is to see how relationships are formed in cases of drug abuse that occur in alumni and students of the University of North Sumatra, and to see what factors cause drug abusers to use drugs. This research method is qualitative with in-depth interviews with key informants and ordinary informants. The results show that there are factors of drug use among alumni and students caused by the influence of friends and seniors. This aims to make it easier to enter the friendship environment on campus. So that the formation of relationships among drug abusers is always changing, utilizing friendships to get drugs, and friendship relationships that are always in conflict. Alumni or students who still use drugs will use their income to obtain drugs, while those who do not have income, for example students, will lie to their families by using the pocket money left by their parents to obtain drugs.